Paramedic Mental Workload in Pandemic Covid-19 Era - Arifianto, Dedy; Fitriasari, Nikma; Mastuti, Ni Luh Putu Herli (Jurnal Kedokteran Brawijaya, 2024)
The number of Covid-19 patients hospitalized continues to increase in line with the increase in Covid-19 cases in Indonesia. The increasing number of Covid-19 patients in hospitals is increasing the workload of paramedics. High workloads will cause saturation and fatigue. In addition, an increase in the number of Covid-19 patients increases anxiety and depression will be infected when treating patients. Paramedics should also use personal protective equipment during shift guards which causes dehydration and discomfort. This situation can degrade the quality of service to patients. The study aims to measure the mental workload of paramedics by NASA-TLX (National Aeronautics and Space Administration Task Load Index) method and find out the factors that affect mental workload levels. This research is a quantitative research with a cross sectional approach. The research was conducted at Hospital X type C in Malang Regency in October 2020. The samples used were all 100 Hospital X paramedics. Research instruments in the form of questionnaires shared through Google Form. Data analysis is done with descriptive analysis and Chi-Square analysis with p value <0.05. The results found paramedics had a low mental workload of 1%, a moderate mental load of 3%, a high mental workload of 47%, and a very high mental workload of 49%. The Chi-Square test results found that age factors had an effect on the mental workload level of paramedics.